2008
DOI: 10.1080/15563650701601790
|View full text |Cite
|
Sign up to set email alerts
|

Blue-ringed octopus (Hapalochlaena sp.) envenomation of a 4-year-old boy: A case report

Abstract: This case report serves as a reminder of how appropriate treatment can ensure discharge from hospital with no long-term consequences. It also highlights the importance of education for beach goers and in particular parents to prevent exposure of tetrodotoxin to children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…A patient that presents with symptoms of respiratory failure should be placed on mechanical ventilation and should receive supportive care (77). Supporting this, a case report of a 4-year-old envenomated by this octopus had a satisfactory outcome with no long-term consequences after prompt intubation and appropriate supportive therapy (78). The affected limb should be elevated and direct pressure should be applied at the site of the attack so the toxin does not spread via the bloodstream, and eventually lymphatic circulation (79,80).…”
Section: Blue-ringed Octopus Envenomation Treatment Recommendationsmentioning
confidence: 91%
“…A patient that presents with symptoms of respiratory failure should be placed on mechanical ventilation and should receive supportive care (77). Supporting this, a case report of a 4-year-old envenomated by this octopus had a satisfactory outcome with no long-term consequences after prompt intubation and appropriate supportive therapy (78). The affected limb should be elevated and direct pressure should be applied at the site of the attack so the toxin does not spread via the bloodstream, and eventually lymphatic circulation (79,80).…”
Section: Blue-ringed Octopus Envenomation Treatment Recommendationsmentioning
confidence: 91%
“…Most species of octopuses cause only mild reactions, such as swelling or redness. 11 However, bites by the blue-ringed octopus (Hapalochlaena maculosa) 8 have been known to lead to severe systemic or even fatal reactions. 7,9,11,12 Its saliva contains a neuromuscular toxin that can be released through its powerful beak 13 and can produce respiratory arrest within minutes.…”
Section: Commentmentioning
confidence: 99%
“…Other symptoms are vomiting, muscle weakness, speech difficulties, visual disturbances, hypotension, and bradycardia. 8,14 The only animal known to survive the effects of this toxin is the octopus itself, but not every bite results in intoxication. 15 In 2002, Taylor et al 5 reported on injuries caused by marine animals in Australia.…”
Section: Commentmentioning
confidence: 99%
“…Moreover, human fatalities occurred by the toxins of the blue ringed octopus, Oxycanus maculosus and Hapalochlaena sp. which contain a powerful neurotoxin that caused respiratory arrest and total paralysis (Bonnet, 1999;Cavazzoni et al, 2008). Experimentally, the PSG extract of Octopus aegina showed anticancer activity in vitro and in vivo cancer models (Karthigayan et al, 2006).…”
Section: Introductionmentioning
confidence: 98%